වෘත්තීය සැලසුම්කරණය - Ishanka, B.T.; Jayantha, J.; Rathnayaka, J.; Tharunya, R.; Thilakarathna, H.P.W.L. (University of Sri Jayewardenepura, Nugegoda, 2013)
Pdf is attached
Vruththeeya Salasumkaranaya